ANALYSIS OF CHARACTERIZATION OF THE MAIN CHARACTERS OF “FIRST THEY KILLED MY FATHER” MOVIE BY ANGELINA JOLIE - Trisnian Ifianti (Journey: Journal of English Language and Pedagogy, 2020)
Literary work, especially film, gives life a lot of inspiration. Movie makes the reader aware that the story that happens in a movie is a reflection of a real life. Characters are characters in stories, and traits are the reasons why a character does things. In fact, there are several explanations why in the Movie Script "First They Killed My Father," the researcher was interested in studying literature on cinema, first this film had some amazing characters. Secondly, this film will encourage everybody to fight arbitrariness and anti violent campaigns.. Statements of the problem of research are: What is the physical appearance of the main characters, how is the main character's personality, how are the main characters ' social status, how are the main characters’ social relations. This study is intended to clarify the presence of the main characters, their personality, the social position of the main characters, their social relationship with the main characters. The method used in this study is qualitative research, and the findings of the investigations are all phrases and dialogs between characteristics related to the characterization of the film. The results of this research show that the main characters Loung Ung and Pa, Loung Ung’s Father, named Mr. Ung have made a great contribution to the plot. Characterization concerns the main characters ' physical appearance, personality and social status. Loung Ung’s physical appearance are little girl, slender build, average hair, caramel skin. Pa or Mr. Ung physical appearances are average build, male, moon shape eyes, and caramel skin. Both of the main character have brave personalities, love and care, and love the whole family. For the social status they are moderate family and live in apartment in the city . Pa or Mr.Ung is well educated person because he is an officer. Pa or Mr.Ung has a good social relationship with the people surrounding, but Loung Ung doesn’t have a good social relationship with the people surrounding her because she is passive.